The Influence of Compensation And Work-Life Balance On Work Productivity Through Employee Resilience - Priyono, Agung; Dwi Astuti, Nani; Saryatmo, Agung; Darmawan Putra, Awang; Haikal, Fahri (Jurnal Manajemen dan Inovasi (MANOVA), 2026)
Abstract Objective – This study aims to examine the influence of compensation and work-life balance on employee work productivity among the sandwich generation in South Jakarta, and to analyze the mediating role of employee resilience in these relationships. Design/methodology/approach – A quantitative descriptive approach was employed using a questionnaire distributed to 96 respondents identified as sandwich-generation workers. Data were analyzed using Structural Equation Modelling–Partial Least Squares (SEM-PLS) to evaluate both direct and indirect effects among the variables. Findings – The results reveal that compensation and resilience significantly affect employee productivity. Employee resilience was also found to mediate the relationship between compensation and work-life balance with work productivity. However, work-life balance does not directly influence productivity without the mediating role of resilience. These findings highlight that productivity among sandwich-generation employees is driven not only by financial rewards but also by psychological strength and adaptability. Research limitations/implications – This study is limited to respondents in the South Jakarta area with a relatively small sample size, which may limit generalizability. Future research is encouraged to expand to other sectors and regions, and to explore additional variables such as job stress, psychological well-being, and employee engagement. Practical implications – Organizations are advised to enhance compensation strategies, provide flexible work policies, and implement mental health and resilience development programs in order to support the productivity of sandwich-generation employees who carry dual family responsibilities. Originality/value – This research contributes a novel empirical model by integrating employee resilience as a mediating variable in the relationship between compensation, work-life balance, and productivity—a perspective that remains underexplored, particularly within the Indonesian sandwich-generation workforce context. The findings provide valuable insights to guide more effective and human-centered human resource policies.